Impacto de metodologias de ensino e gênero na aprendizagem: uso de metodologias ativas em Fundamentos de Eletromagnetismo - Tais Bastani Ribeiro (2023)
Active methodologies are alternatives to traditional classes used with the purpose of enhance students’ learning. Researches study the impact of active methodologies on conceptual learning, retention of students and gender gap, phenomenon in which women consistently score lower than men in Physics assessments. Among the most used active methodologies in Physics teaching is Peer Instruction (PI), which consists of preparatory activities before the class and group discussions during class. PI is used in a introductory Physics course of Universidade Federal de Minas Gerais, and this use was adapted during the period of Emergency Remote Teaching (ERT), during the COVID-19 pandemic. In this work, we compare the conceptual learning and the final grade of students in traditional classes, PI classes and ERT. We also compare the conceptual learning and course scores by gender in each methodology. For this, we applied the Brief Electricity and Magnetism Assessment (BEMA) in the first and last class of the course, with a pretest and posttest design, for 353 students of traditional classes, 245 students of PI clases and 917 of ERT. From the pretest and posttest, we calculated, for each methodology and gender, the normalized gain g, Cohen’s d from BEMA, the distribution for the final grade and g and compared these distributions with the relative distribution method. On the data analysis, we see a relative increase on the mean gain of 32% with the use of PI, however we don’t see this increase on the final grade. On the ERT, there is a significant increase on the final grade compared to the other two methodologies, but g is similar to g in traditional classes. When separating g from ERT by semester, we see a decrease in each semester, being much lower in the last semester. When separating these data by gender, we see a gender gap in all methodologies, and we found evidence that PI might have a smaller gender gap, but it’s still significant. There isn’t a gender gap in final grades in neither of the methodologies. Overall, we conclude that the use of PI improves students’ conceptual learning, and that teaching during the ERT is less effective over the semesters. The final score in a course is not a good parameter for comparing learning between different groups. Finally, we see that the use of active methodologies may help decreasing gender gap, but not by a large amount.